Insect Pollinator Diversity and Significance of Pollen Resources in Urban Landscape - Ab. Hamid, Suhaila; Azwari, Nadia Aqilah; Elias, Nurul Ain; Rahim, Ahmad Mustaqim (Journal of Sustainable Natural Resources, 2025)
Insects are the most common pollinators of flowering plants. Urban landscape often lacks of flora diversity, potentially limiting the pollinators’ population; thus, flowering plants would face a great decline, and this may reduce the habitat diversity of nature. Therefore, this study was conducted to determine insect pollinators in selected parks in the urban area of Penang Island and its floral source. Insect trapping using light traps and sweep nets was carried out and a total of 65 families from 10 orders were collected from three parks: Youth Park, Botanic Garden and Moon Gate in Penang. Out of that, 13 families were determined as pollinators. Insects from the order Lepidoptera, Coleoptera, Hymenoptera and Hemiptera were the principal representative orders in all study areas. Diurnal insects reported three pollen types; predominant (eight pollen species), secondary (nine pollen species) and important minor (one pollen species) while nocturnal insects recorded the Apidae family with four pollen types; predominant (13 pollen species) secondary (five pollen species), important minor (six pollen species) and minor (two pollen species). The presence of insect pollinators in urban areas suggests that such environments can play a significant role in supporting insect biodiversity that will survive in the urban landscape with nature-based.